2022
DOI: 10.1002/jsfa.12006
|View full text |Cite
|
Sign up to set email alerts
|

Fish proteins as potential precursors of taste‐active compounds: an in silico study

Abstract: BACKGROUND: Fish protein is a good source of amino acids and peptides with sensory properties. Theoretically, the type of protein affects the taste quality of the protein hydrolysates. To better use fish protein in the food ingredients industry, an in silico approach was adopted to evaluate the potential of fish protein to release taste-active compounds.RESULTS: Six types of protein from seven commercial fishes were screened from the Uniprot knowledge base. The results showed that a remarkable number of umami … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The results showed that CGC contains relatively high levels of glutamic acid, aspartic acid, lysine, leucine, and arginine. Glutamic acid and aspartic acid are especially crucial, as they comprise the key amino acids responsible for the savory taste perceived by humans—the “umami" flavour—significantly enhancing the overall flavour of food and imparting a more tantalizing taste to fish ( Hu et al, 2022 ). Moreover, lysine and arginine play crucial roles in protein crosslinking during the processing process.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that CGC contains relatively high levels of glutamic acid, aspartic acid, lysine, leucine, and arginine. Glutamic acid and aspartic acid are especially crucial, as they comprise the key amino acids responsible for the savory taste perceived by humans—the “umami" flavour—significantly enhancing the overall flavour of food and imparting a more tantalizing taste to fish ( Hu et al, 2022 ). Moreover, lysine and arginine play crucial roles in protein crosslinking during the processing process.…”
Section: Discussionmentioning
confidence: 99%